The type of fortificant and the leaf matrix both influence iron and zinc bioaccessibility in iron-fortified green leafy vegetable sauces from Burkina Faso. Issue 2 (20th January 2016) - Icard-Vernière, C.; Picq, C.; Courbis, L.; Mouquet-Rivier, C.
Abstract : Leafy vegetable sauces from Burkina Faso were assessed as a potential vehicle for food fortification. Abstract : Leafy vegetable sauces from Burkina Faso were assessed as a potential vehicle for food fortification. First, iron and zinc bioaccessibility were measured by dialysability method in amaranth and Jew's mallow sauces and in traditional whole dishes consisting of maize paste plus leafy vegetable sauces. Iron dialysability and solubility were higher in amaranth than in Jew's mallow sauce, pointing to a marked effect of the matrix. Iron dialysability was hardly affected by the maize paste contrary to zinc dialysability, which was reduced. Second, iron and zinc bioaccessibility was assessed in the same sauces fortified with NaFeEDTA or iron sulfate. Added iron, i.e. iron supplied by fortification, represented 60% of total iron at the low fortification level and 80% at high level. In amaranth sauces with the high level of fortification using NaFeEDTA and iron sulfate, fractional dialysable iron reached respectively 66% and 26% compared to only 8.1% in the unfortified sauce. Similarly, in Jew's mallow sauces, fractional dialysable iron was 57% and 5% respectively with NaFeEDTA and iron sulfate and less than 1% in the unfortified sauce. Concomitantly, fractional dialysable zinc increased by respectively 20% and 40% in amaranth and Jew's mallow sauces fortified with NaFeEDTA whereas it remained unchanged with iron sulfate. Iron fortification could be an efficient way to greatly increase the available iron content of green leafy vegetable sauces and for this purpose NaFeEDTA is more effective than iron sulfate whatever the food matrix.